Enhancing the Angular Sensitivity of Plasmonic Sensors Using Hyperbolic Metamaterials - Sreekanth, Kandammathe Valiyaveedu (Adv Opt Mater, 2016)
Surface plasmon resonance (SPR) sensors operate mainly on prism and grating coupling techniques, with spectral and angular scans being the two major interrogation schemes. Among them, the angular scan technique has several advantages including higher measurement precision owing to its higher signal-to-noise ratio. The currently available SPR sensor arrangements provide a maximum angular sensitivity of 500°–600° per RIU. Here, we report the study of grating coupled-hyperbolic metamaterial (GC-HMM) sensors with high angular sensitivity. The experimental studies show extraordinary angular sensitivities from visible to near infrared (NIR) wavelengths by exciting bulk plasmon polaritons associated with hyperbolic metamaterials, with a maximum of 7000° per RIU. This angular-scan plasmonic biosensor has been used for the detection of low molecular weight biomolecules such as biotin (244 Da) and high molecular weight macromolecules such as Cowpea mosaic virus (CPMV, 5.6 × 10(6) Da) at ultralow concentrations. The miniaturized sensing device can be integrated with microfluidic systems for the development of next-generation biosensors for lab-on-a-chip and point-of-care applications.